1997
DOI: 10.1002/(sici)1097-4636(199724)38:4<303::aid-jbm2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Factors effecting dental composite wearin vitro

Abstract: The wear of posterior dental composite restorations takes place through a complex combination of wear mechanisms. To isolate and measure the contribution of the different tribological phenomena in a controlled manner, an oral wear simulator was employed. Results previously reported demonstrated the simulator's ability to form strong correlations with clinical results for both abrasion and attrition wear. These results were generated with the device configured to mimic masticatory dynamics, specifically employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…This is because it is difficult to predict the effect of abrasive medium on wear behavior. Some in vitro studies have reported conflicting results with increasing wear with abrasive slurry, hard abrasive particles 33) , or reducing wear with lubrication 34) . The standardization and specification of artificial denture tooth sample in some previous studies were not exactly focused.…”
Section: Discussionmentioning
confidence: 99%
“…This is because it is difficult to predict the effect of abrasive medium on wear behavior. Some in vitro studies have reported conflicting results with increasing wear with abrasive slurry, hard abrasive particles 33) , or reducing wear with lubrication 34) . The standardization and specification of artificial denture tooth sample in some previous studies were not exactly focused.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports about differences in wear resistance among composites, resulting from a combination of factors, such as filler features, organic matrix components, elastic modulus and hardness. 7,13 Among these parameters, load, shape and size of fillers can be stated as …”
Section: Discussionmentioning
confidence: 99%
“…5, the amount of large fillers containing MLV seems to be more than other materials, and cracks were observed around fillers after 40,000 cycles. These protruded large fillers might have experienced greater friction with medium or the stylus tip during each wear testing, which led to accelerative wear, as shown in previous studies 6,12,16,17,19,20) . Although the two-body wear test in the current study was carried out without medium, the exfoliated fillers may have acted as an abrasive medium.…”
Section: Discussionmentioning
confidence: 76%